2013
DOI: 10.3389/fnhum.2013.00519
|View full text |Cite
|
Sign up to set email alerts
|

Don't words come easy? A psychophysical exploration of word superiority

Abstract: Words are made of letters, and yet sometimes it is easier to identify a word than a single letter. This word superiority effect (WSE) has been observed when written stimuli are presented very briefly or degraded by visual noise. We compare performance with letters and words in three experiments, to explore the extents and limits of the WSE. Using a carefully controlled list of three letter words, we show that a WSE can be revealed in vocal reaction times even to undegraded stimuli. With a novel combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…In a recent study of young normal subjects, using the same two experimental paradigms, we observed a significant word superiority effect in both naming and visual processing (Starrfelt, Petersen, & Vangkilde, 2013).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In a recent study of young normal subjects, using the same two experimental paradigms, we observed a significant word superiority effect in both naming and visual processing (Starrfelt, Petersen, & Vangkilde, 2013).…”
Section: Discussionmentioning
confidence: 79%
“…Using the same tasks and stimuli with normal readers, we have recently shown that the WSE can be revealed both in the naming and in the perception task (Starrfelt, Petersen, & Vangkilde, 2013). With the present study we investigate whether the word superiority effect is eliminated or reversed in patients with pure alexia, and whether abnormal performance is differentially reflected in the naming task or the perceptual (accuracy-based) task.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Starrfelt et al (2013) explored the word superiority effect, which refers to the observation that when written stimuli are degraded by noise or brief presentation, letters in words are reported more accurately than single letters and letters embedded in non-words. With a novel combination of psychophysics and mathematical modeling, they showed that word superiority is due to single words being simply processed faster than single letters (at least for simple short words).…”
mentioning
confidence: 99%